From Traditional to AI-Augmented Project Management: Rethinking Governance and Managerial Roles - Kocet, Aljaž; Vrečko, Igor (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The rapid diffusion of artificial intelligence (AI) is fundamentally reshaping managerial work and governance structures in project-based organizations. As projects increasingly function as primary vehicles for digital and sustainability-driven transformation, traditional project management models - grounded in linear planning, human-centered decision-making, and static governance arrangements - face growing limitations in coping with heightened complexity, uncertainty, and interdependence. While existing research has largely focused on AI as a technical tool for improving forecasting, monitoring, and operational efficiency, its broader implications for project governance and managerial roles remain underexplored. This conceptual paper examines the transition from traditional to AI-augmented project management through a systematic synthesis of literature from project management, organizational governance, decision-making, and artificial intelligence. The analysis highlights how AI reshapes key phases of the project lifecycle, alters decision-making logics, and reconfigures the role of the project manager from a primary decision-maker toward a sense maker, orchestrator, and steward of AI-supported decisions. Building on this synthesis, the paper introduces the concept of AI-augmented project governance as a theoretical framework that addresses emerging challenges related to accountability, transparency, and alignment with sustainability and ESG principles. The paper concludes by outlining implications for project management theory and proposing directions for future empirical research.